The Role of Financial Literacy in Moderating the Influence of Digital Payments and Lifestyle on Financial Management Behavior of Generation Z in Palu City - Muhammad Ilham Pakawaru; Mohammad Iqbal Bakry; Muliati; Yuldi Mile; Andi Ainil Mufidah Tanra (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2025)
Purpose – This study aims to examine the role of financial literacy in moderating the influence of digital payments and lifestyle on the financial management behaviour of Generation Z in Palu City. Design/methodology/approach – The sample consisted of 210 Generation Z respondents residing in Palu who use digital or non-cash payment methods in their transactions. Data were analysed using WarpPLS 7.0. Originality - These findings highlight that good financial literacy helps individuals recognise the impact of lifestyle on their finances and take appropriate steps to manage expenditures more effectively as a form of self-control. Findings and Discussion – The results show that digital payments have a direct influence on the financial management behaviour of Generation Z in Palu City, while lifestyle has no direct effect. Financial literacy weakens the impact of lifestyle on financial management behaviour, but strengthens the impact of digital payments on financial management behaviour. The adoption of digital payments reflects Generation Z’s adaptation to technological developments that increasingly promote non-cash transactions in Palu and Indonesia in general, providing convenience in payment processes. Conclusion – This study implies that financial literacy can serve as a controlling factor (a tangible form of perceived behavioural control), bridging the gap between consumptive intentions and actual behaviour. For this reason, the government and financial institutions may employ financial literacy as a preventive strategy to mitigate debt-related issues, particularly among younger generations with digital and consumptive lifestyles.